2023
DOI: 10.3390/cancers15041260
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Optimizing Radiation Therapy Decisions in Early Invasive Breast Cancer

Abstract: Adjuvant whole breast irradiation after breast-conserving surgery is a well-established treatment standard for early invasive breast cancer. Screening, early diagnosis, refinement in surgical techniques, the knowledge of new and specific molecular prognostic factors, and now the standard use of more effective neo/adjuvant systemic therapies have proven instrumental in reducing the rates of locoregional relapses. This underscores the need for reliably identifying women with such low-risk disease burdens in whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 183 publications
0
12
0
Order By: Relevance
“…Young age is a known risk factor for long-term survival in patients who undergo breast-conserving surgery and are not treated with NAC [31,32]. This view was veri ed by a meta-analysis of large-scale prospective tests of breast-conserving surgery, which suggested that younger female patients had a higher 10-year locoregional recurrence rate(LRR) [33]. Nevertheless, once the patients were treated with NAC, we could not able to assess the role of age in predicting survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Young age is a known risk factor for long-term survival in patients who undergo breast-conserving surgery and are not treated with NAC [31,32]. This view was veri ed by a meta-analysis of large-scale prospective tests of breast-conserving surgery, which suggested that younger female patients had a higher 10-year locoregional recurrence rate(LRR) [33]. Nevertheless, once the patients were treated with NAC, we could not able to assess the role of age in predicting survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant whole‐breast radiation to the conserved breast is the standard of care for early invasive breast cancer. The benefits of adjuvant radiation in reducing the risk of relapse and breast cancer‐associated mortality 1,2 must be balanced against the risks of acute and late radiation‐induced adverse effects 3 …”
Section: Introductionmentioning
confidence: 99%
“…The use of validated biomarkers to guide adjuvant radiation therapy decisions is not well established and the American Society of Clinical Oncology maintains that clinicopathological factors are not sufficient in themselves to identify women <70 years of age whose risk is sufficiently low that adjuvant radiation after breast‐conserving surgery can be safely avoided. Thus, biomarker‐driven de‐escalation of radiation in low‐risk patients (T ≤ 2 cm, node‐negative, estrogen receptor/progesterone receptor [ER/PR]‐positive, and HER2‐negative) is under active investigation 3 . In this context, Ki67 represents a widely available, inexpensive biomarker that can be used to identify a molecularly low‐risk group 4 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations